1999
DOI: 10.1111/j.1572-0241.1999.01427.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Upper Gastrointestinal Symptoms in The Canadian Population: Findings From The Digest Study

Abstract: Upper GI symptoms are very prevalent in the general Canadian population and substantially affect the quality-of-life and psychological well-being of those affected. Dysmotility-like symptoms, rather than heartburn, are the most common chronic upper gastrointestinal symptoms in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 27 publications
4
66
1
1
Order By: Relevance
“…In this study coffee or tea intake has not been shown to be related to the presence of Dyspepsia similarly studied in rural Asia [57]. In addition, some western studies have reported that excessive coffee or tea intake has not been shown to be related to the presence of Dyspepsia [58,59].…”
Section: Discussionmentioning
confidence: 81%
“…In this study coffee or tea intake has not been shown to be related to the presence of Dyspepsia similarly studied in rural Asia [57]. In addition, some western studies have reported that excessive coffee or tea intake has not been shown to be related to the presence of Dyspepsia [58,59].…”
Section: Discussionmentioning
confidence: 81%
“…QOL in patients with RE is lower than that in patients with heart failure (mild) and angina pectoris [20]. It is known that QOL in patients with FD is also decreased [1,2] and may be as low as patients with RE due to upper abdominal symptoms. Once symptoms are relieved by PPI treatment, improvement of QOL in patients with upper abdominal symptoms is expected.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of patients, symptoms are mild and can be controlled by over-the-counter drugs. The rest of the patients visiting hospitals have severer symptoms and decreased quality of life (QOL) [1,2], but their symptoms are not always treated satisfactorily. Patients usually have variety of symptoms and it sometimes makes physicians felt difficulty to select adequate treatment unless the symptoms are clearly accounted to organic disease, leaving patients in an undesirable condition.…”
Section: Introductionmentioning
confidence: 99%
“…8 Both in the general population and in tertiary care, the most prevalent symptoms are postprandial fullness, epigastric pain, early satiety, and nausea. [9][10][11][12][13] However, there is considerable heterogeneity in the symptom pattern, both in number and type of symptoms. 14 …”
Section: 5-7mentioning
confidence: 99%